Using CFD analysis to evaluate the performance of a natural gas compressor under different geometries of internal parts - Rong Liu; AliB.M. Ali; Dheyaa J. Jasim; Narinderjit Singh Sawaran Singh; Mohammed Al-Bahrani; Zubair Ahmad; Omid Ali Akbari; Soheil Salahshour; Ali Mohammadi Hasanabad (Case Studies in Thermal Engineering)
Natural gas transmission networks in some countries are the main arteries of this energy source. Their extensiveness and the fluid properties of natural gas necessitate proper compression under all conditions. The design of pressure boosting stations and the operation prediction under different consumer demand conditions necessitate using several parallel compressors capable of different rotational speeds. In this study, a model of a heavy-duty centrifugal compressor used in these stations has been studied. First, using the finite volume method, the compressor is simulated with initial conditions and in three dimensions. Then, suggestions are made to modify the geometry of its various parts, and their effects under all flow rates and rotational speeds are examined. The impact of the number of blades/vanes in the impellers, the intermediate diffuser, and the inlet channel has been studied. The effect of using splitters has also been examined. The results show that although the use of splitters is not recommended, changing the number of blades/vanes in other parts can increase the efficiency of the compressor. Increasing the number of IGVs reduces the compressor power consumption by 5.9 %. Increasing the number of IBs from 15 to 18 for the first and second stages increases the outlet pressure by 2.93 % and 0.32 %, respectively. It also decreases the outlet entropy by 46.80 % and 28.45 %, respectively. It also decreased TKE in the first stage from 172.83J/K to 139.26J/K (19.99 %) and increased it from −52.73 to 4.77J/K in the second stage. Reducing the number of diffuser vanes to 19 increased the efficiency by 1.1 %. Reducing the number of IBs to 15 increased the efficiency by 2.55 %. In general, since the natural gas consumption flow rate has changed from the initial design conditions, and the performance improvement resulting from the proposed modifications is greater at higher flow rates, these changes are justified.